ACHIEVEMENT MOTIVATION AND ITS RELATIONSHIP WITH JUMP SHOT ACCURACY IN BASKETBALL AMONG FOURTH-YEAR STUDENTS AT THE COLLEGE OF PHYSICAL EDUCATION AND SPORTS SCIENCES, UNIVERSITY OF KIRKUK - M. Ibrahim Bahram Khorshid Muhammad Ali (Proximus Journal Publishing, 2025)
The aim of this research is to identify the level of achievement motivation among fourth-year students at the College of Physical Education and Sports Sciences, University of Kirkuk, to assess the jump shot accuracy in basketball among the sample members, and to determine the correlation between achievement motivation and jump shot accuracy in basketball. The researcher used a descriptive method with a correlational approach, which is suitable for the nature of the research. The study population was chosen using a purposive method from fourth-year students at the College of Physical Education and Sports Sciences at the University of Kirkuk for the academic year 2023/2024, divided into six sections, with a total of 210 students. The sample was selected randomly from section (C) of the fourth-year day study, consisting of forty-two students, which represents 20% of the total population. Considering the results discussion, the researcher concluded the following: There is no correlation between the psychological variable, achievement motivation, and jump shot accuracy among the sample members. However, there is a positive relationship between achievement motivation and jump shot accuracy in basketball, where students with high motivation achieve more accurate shooting rates. Achievement motivation directly affects the student's focus during shooting, which leads to improved skill performance under competitive pressure. Students with high achievement motivation show a greater ability to endure challenges and correct mistakes during shooting. Based on these conclusions, the researcher recommends that teachers consider the psychological factors when preparing educational programs and developing motivational traits to achieve success. Furthermore, the researcher advises developing the tests used in the study to understand achievement motivation and performance skills in students across various sports
Keywords: Achievement Motivation; Accuracy; Jump Shot